Word order and context in sentence processing: evidence from L1 and L2 Russian - Slioussar, Natalia; Harchevnik, Maria (Frontiers in Psychology, 2024)
In this study, we compared how native speakers of Russian and speakers of Mandarin Chinese learning Russian as a foreign language process Russian sentences with SVO (canonical) and OVS (non-canonical) word orders in isolation (Experiment 1) and in context (Experiment 2). One-sentence contexts introduced one NP mentioned in the target sentence, either the first (so that given information preceded new information, which is characteristic for Russian and many other languages) or the second. We used different measures to capture online and offline effects: word-byword reading times, question-answering accuracy and sentence rating on a 1 to 5 scale (for L1 participants).In both experiments, RTs and question-answering accuracy data showed that non-canonical orders were difficult for L2 participants, but not for L1 participants. However, L1 participants gave noncanonical orders lower ratings in isolation, presumably because in naturally occurring texts, they are used only in particular contexts. As for the context factor in Experiment 2, some effects were the same for L1 and L2 processing: all participants read given NPs faster than new ones and preferred sentences with a 'given -new' word order. The latter may reflect the universal principles of narrative coherence. However, unlike native speakers, L2 readers are not sensitive to more subtle contextual requirements of different word orders.